Harmony of Knowledge & Faith: Methods and Studies in Islamic Educational Psychology - Chairunnisa C; Vivik Shofiah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
In a dynamic global era full of multidimensional challenges, education is required to focus not only on academic aspects, but also to develop the moral, social, and spiritual qualities of students in a balanced manner. Islamic educational psychology offers an integrative framework by combining theories of developmental and learning psychology with the principles of Islamic teachings. The research method used was descriptive qualitative with a literature study (library research). The results of the study show that Islamic educational psychology integrates modern psychological theories such as behaviourism, cognitive, and humanistic with the principles of the Qur'an and Sunnah. The main principles applied include the development of natural potential, tawhid, exemplary behaviour (uswah hasanah), compassion (rahmah), and the process of purification of the soul (tazkiyah al-nafs). Islamic educational psychology provides a comprehensive basis for developing learning that focuses not only on cognition, but also on the balanced formation of character and spirituality.